The degree of food processing is associated with anthropometric measures of obesity in Canadian families with preschool-aged children - Ashraf, Rahbika; Duncan, Alison M.; Darlington, Gerarda; Buchholz, Andrea C.; Haines, Jess; Ma, David W. L. (Frontiers in Nutrition, 2022)
Adopting a healthy diet remains central for the prevention of obesity. In adults, higher intake of ultra-processed food is associated with a greater risk of overweight and obesity. However, little is known about the degree of food processing and its association with anthropometric measures in families with preschool-aged children, a critical period for the development of dietary patterns. This cross-sectional study included preschool-aged children (n = 267) between 1.5 and 5 years of age and their parents (n = 365) from 242 families enrolled in the Guelph Family Health Study. Dietary assessment was completed using ASA24-Canada-2016. Foods and beverages were classified based on their degree of food processing using the NOVA Classification (unprocessed or minimally processed foods, processed culinary ingredients, processed foods, and ultra-processed foods). Associations between the energy contribution (% kcal) of each NOVA category and anthropometric measures were examined using linear regression models with generalized estimating equations, adjusted for sociodemographic variables. The energy contribution of ultra-processed foods was the highest relative to the other NOVA categories among parents (44.3%) and children (41.3%). The energy contribution of unprocessed or minimally processed foods was 29.1% for parents and 35.3% for children, processed foods was 24.0% for parents and 21.3% for children, and processed culinary ingredients was 2.6% for parents and 2.1% for children. Ultra-processed foods (% kcal) were positively associated with BMI (β = 0.04, 95% CI: 0.01 to 0.07, P = 0.02), waist circumference (β = 0.11, 95% CI: 0.03 to 0.18, P = 0.008) and body weight (β = 0.13, 95% CI: 0.03 to 0.22, P = 0.01) in parents, but not children. Unprocessed foods (% kcal) were negatively associated with waist circumference in parents (β = -0.09, 95% CI: -0.18 to -0.01, P = 0.03) and children (β = -0.03, 95% CI: -0.05 to -0.01, P = 0.01), as well as body weight (β = -0.12, 95% CI: -0.23 to 0.00, P = 0.04) in parents. The degree of food processing primarily influenced anthropometric outcomes in parents. Nevertheless, diets of children were similar, suggesting that such exposure in families may eventually lead to outcomes observed in parents.